KESEDIAAN PELAJAR TINGKATAN EMPAT MEMPELAJARI MATA PELAJARAN PENGAJIAN KEJURUTERAAN AWAM (Sains Humanika, 2008)
This research was carried out to study the student’s readiness in the aspect of interest, English Language skills and the prior knowledge towards learning in Civil Engineering Studies at Menengah Teknik Seri Iskandar. This descriptive reseoafrch involved 78 responden of form four students in the session of 2007 who enrolled in the Civil Engineering Course. Questionnaire was used as an instrument in this research with the reliability at α = 0.906. Raw data was analyzed by using Statistical Packages for the Social Sciences 13.0 (SPSS) in order to get the frequency, percentage and mean of the data. The result shows that the student’s readiness towards learning in Civil Engineering Studies at Sekolah Menengah Teknik Seri Iskandar were at a medium level in the aspect of interest, English Language skills and their prior knowledge. Result of t–test shows that, there are no different between genders in the aspect of interest and English Language skills towards the learning in Civil Engineering Studies. On the other hand, there is a different between genders in the aspect of prior knowledge towards the learning of Civil Engineering Studies. It is hoped that the findings can be used as a guide for schools, State of Education Department (JPN) and Ministry of Education Malaysia (KPM) in order to help students that enrolled to this subject and as well as other technical subjects.
Keywords: Readiness; interest; skills; prior knowledge